Pandangan Masyarakat Terhadap Dukun Sebagai Pengobatan Kesehatan Dalam Perspektif Aqidah Islam Studi Kasus Pada Kabupaten Tapanuli Selatan - Siregar, Ardiansyah; Junaidi, Junaidi (Jayapangus Press, 2024)
The background of this research is treatment by traditional healers, as an alternative for people who find it difficult to access modern medicine. People in Pargarutan Julu Village seek alternative traditional medicine because they are faced with health problems that are difficult to solve medically, indicating dissatisfaction or unmet needs in the modern health system. The purpose of the study is to find out the community's views on the practice of traditional healers as a form of health treatment has become a subject of complex debate, especially in the context of Islamic aqeedah. This paper investigates people's views on shamans as a form of health treatment, focusing on the perspective of Islamic aqidah. The research method is a qualitative approach and literature analysis. The results show that people's views on traditional healers are influenced by cultural factors, traditions, and lack of understanding of Islamic teachings. The informant mentioned that taking treatment from a shaman is part of shirk treatment. Therefore, there is a need for a better educational approach and religious understanding in the community to overcome the wrong perception of shamans and increase understanding of the correct Islamic aqidah in the context of health treatment.